2017
DOI: 10.1038/s41598-017-06684-0
|View full text |Cite
|
Sign up to set email alerts
|

Sustained efficacy of closed loop electrical stimulation for long-term treatment of absence epilepsy in rats

Abstract: Closed-loop brain stimulation is a promising alternative to treat drug-resistant epilepsies. In contrast to optogenetic interventions, transcranial electrical stimulation (TES) does not require cellular modification of neurons to be effective, and it is less invasive compared to deep brain stimulation. Furthermore, on-demand TES of targeted brain regions allows the potential for normal function of these networks during interictal periods, a possibility that is eliminated by resective surgical treatment approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 52 publications
0
77
0
Order By: Relevance
“…The animals for longitudinal observations (n ϭ 5, three months old), animals for pharmacological experiments (n ϭ 3, five to seven months) and animals for transcranial electrical stimulation experiments (n ϭ 6, five to seven months) were implanted with intracortical recording electrode triplets (interwire spacing, 0.4 mm), which targeted the frontal and parietal cortical areas of both hemispheres and unilaterally the CA1 subfield of the hippocampus, as already reported elsewhere in details (Kozák and Berényi, 2017). For transcranial stimulation experiments, additional stimulation electrodes were implanted over the temporal bone bilaterally (Kozák and Berényi, 2017;Kozák et al, 2018). Unit recordings and intracortical stimulation experiments were performed in rats divided into two age groups: juvenile (2.5-4 months, n ϭ 5) and mature (five to seven months, n ϭ 4) animals.…”
Section: Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…The animals for longitudinal observations (n ϭ 5, three months old), animals for pharmacological experiments (n ϭ 3, five to seven months) and animals for transcranial electrical stimulation experiments (n ϭ 6, five to seven months) were implanted with intracortical recording electrode triplets (interwire spacing, 0.4 mm), which targeted the frontal and parietal cortical areas of both hemispheres and unilaterally the CA1 subfield of the hippocampus, as already reported elsewhere in details (Kozák and Berényi, 2017). For transcranial stimulation experiments, additional stimulation electrodes were implanted over the temporal bone bilaterally (Kozák and Berényi, 2017;Kozák et al, 2018). Unit recordings and intracortical stimulation experiments were performed in rats divided into two age groups: juvenile (2.5-4 months, n ϭ 5) and mature (five to seven months, n ϭ 4) animals.…”
Section: Surgerymentioning
confidence: 99%
“…All recording sessions took place in the same room in 12/12 h light/dark cycles. After recovery from the surgery (minimum 3 d), the maturing rats were connected to the recording system and were observed for three months continuously in their home cage, as reported elsewhere already (Kozák and Berényi, 2017). The neuronal signals were preamplified, amplified (total gain 400ϫ), multiplexed on head and stored after digitalization at 20-kHz sampling rate per channel (KJE-1001, Amplipex).…”
Section: Electrophysiological Recordings and Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we combine the design principles from state‐of‐the‐art ECoG devices and electrophoretic drug delivery devices to present a cortical device that can simultaneously deliver drugs and record local neural activity. This represents a significant advancement in cortical devices for neural interfacing as the ability to monitor neural activity in real time can greatly enhance the efficacy of drug treatment regimens . The device design is presented in Figure 1 with arrows and text marking the primary components including the electrode pads for connecting to an external recording system, the source and target pads for connecting to the source and target electrodes of the µFIP as well as the fluidic inlet/outlet for loading/exchanging the drug solution (see the Experimental Section for fabrication details).…”
mentioning
confidence: 99%
“…us, the research of absence epilepsy is significant and far-reaching. e most common treatment for epilepsy now remains in drug-assisted or surgical resection [16]. In some investigations, it has been shown that long-term service of epilepsy drugs may lead to liver decline or even damage due to epilepsy is a long-term chronic disease [17,18].…”
Section: Introductionmentioning
confidence: 99%